2016
DOI: 10.1002/hed.24384
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic thyroid cancer: Prognostic factors, patterns of care, and overall survival

Abstract: Even after correction for selection and immortal time bias, high-dose RT resulted in improved survival. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2083-E2090, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
108
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 37 publications
14
108
0
1
Order By: Relevance
“…Sugitani et al [6] reported that a total radiation dose ≥40 Gy was an independent predictor for OS, and Dumke et al [7] reported that a total radiation dose ≥50 Gy was a significant predictor for OS in univariate analysis. Glaser et al [10] compared three total radiation dose groups, ≤36 Gy, 36.1-59.3 Gy, and ≥59.4 Gy, and reported that a total radiation dose ≥59. 4 Gy was an independent predictor for OS in 3,552 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugitani et al [6] reported that a total radiation dose ≥40 Gy was an independent predictor for OS, and Dumke et al [7] reported that a total radiation dose ≥50 Gy was a significant predictor for OS in univariate analysis. Glaser et al [10] compared three total radiation dose groups, ≤36 Gy, 36.1-59.3 Gy, and ≥59.4 Gy, and reported that a total radiation dose ≥59. 4 Gy was an independent predictor for OS in 3,552 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS in their study was 9.3 months. Glaser et al [10] and Pezzi et al [11] reported that radiotherapy with a high total dose improved the OS of ATC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Taxanes, doxorubicin, and platins have shown activity as a single or combined agents with response rates ranging from 15% to 25% 41 . The combined RT and chemotherapy regimens with doxorubicin with or without taxanes or cisplatin combined with RT have shown the most promising results 19,42 . In the current study, chemotherapy was administered to few patients (n=7) and did not influence OS.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis, identified white blood cell count, surgery, and post-operative RT as independent prognostic factors in ATC patients. According to Glaser et al, age and tumor size may be prognostic factors in ATC patients 19 . Our results did not identify sex, stage, surgery or RT as significant predictors of survival by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation